Scrophulariaceae endémicas del Perú - León, Blanca (2006)
The Scrophulariaceae are represented in Peru by around 18 genera and 35 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly herbs. Here we recognize two endemic species in two genera, these species are found mainly in Humid Lowland Amazonian Forests, between 200 and 1000 m elevation. None of Scrophulariaceae endemic has been recorded within Peru’s protected areas system.